EXPECTANT MOTHERS’ KNOWLEDGE ABOUT BREAST FEEDING BEFORE AND AFTER HEALTH EDUCATION AT PAGESANGAN HEALTH CENTER - Baiq Iin Rumintang; Rita Sopiatun; Della Trismaningsih (poltekkes kemenkes mataram, 2016)
Abstract : ASI (the mother’s breast-feeding) is a food which is important for brain growth, health staffs must provide information and education of exclusive breast-feeding to the mothers since pregnancy tests until the period of exclusive breast-feeding is complete. According to SDKI (demographics survey and Indonesian health) the exclusive breast-feeding below 6 months by 41% because many babies who have consumed the formula for infants at the age of below than 6 months. The purpose of the study was to compare pregnant women’s knowledge level about breast-feeding before and after health education at Pagesangan health center 2016. The research was a Quasi Experiment with research design, time series design. The population in this study was the third trimester pregnant women. The research technique was purposive sampling with a sample of 45 people and using Marginal Homogenity Test (Wilcoxon). Based on the result of the research, the highest expectant mother’s knowledge before health education was in terms of low category as many as 38 people (84.4%) and after the health education, the highest maternal knowledge on medium category was 21 people (46.7%). The statistical analysis was obtained probability value (p value) = 0.00 where the value was smaller than the significance level of 0.05 (0.00) hence it can be concluded that there was a significant comparison between knowledge before and after health education. It is expected to Pagesangan health center can improve the service quality in providing health education to set a schedule of counseling routinely and equip the facilities to provide lefleat on how to squeeze and store ASI.